(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Intestinal tuberculosis (ITB) have significant immunological similarity with Crohn’s disease (CD). T helper cells and various cytokines secreted by them play a very crucial role in the pathogenesis of both the diseases. It is of great clinical relevance in a country like India to perform a comparative study between CD and ITB with respect to pathogenesis. Objectives: To study the levels of four cytokines(IL-4,IL-17, IFN-ϒ & TGF-β1 ) s in serum of patients with CD & ITB which indirectly reflects the levels of CD4+ T cells. Material and method: An observational, cross-sectional study was done on patients, attending Gastroenterolory clinic in a tertiary care hospital, with features of ileitis, colitis or ileo-colitis due to CD or ITB.12 cases of Crohn’s disease & 13 cases of intestinal tuberculosis were taken( control-20 cases). 5 biopsies were taken from the ulcerated mucosa & 3 biopsies were taken from normal mucosa. H & E study & serum levels of four cytokines(IL-4,IL-17, IFN-ϒ & TGF-β1 ) were estimated. Results & analysis: In CD & ITB we found marginal increase of IFN-ϒ & TGF-β1 compared to control. IL17 level was found decreased in ITB compared to control (p=0.001).CD4+ T cells study by ELISA also showed significant increase in the concentration of IFN-γ (p=0.007) in ITB. There was no change in IL4 levels. Conclusion: Cytokines have an important role in the pathogenesis of grannulomatuos inflammatory bowel diseases. The identification of cytokines & their role in the pathogenesis might be helpful for future therapy based on cytokines, and anti-cytokine antibodies. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.784-789